PENGARUH PROFITABILITAS, UKURAN PERUSAHAAN DAN PENGHARGAAN TERHADAP PENGUNGKAPAN TANGGUNG JAWAB SOSIAL PERUSAHAAN (Studi pada Perusahaan Manufaktur di Bidang Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia Tahun 2018-2020) - Siti Raudatul Jannah; Aditya Septiani (Diponegoro Journal of Accounting, 2022)
This study aims to examine the effect of profitability, company size, and rewards on the corporate social responsibility disclosure of manufacturing companies in the food and beverage sector listed on the Indonesia Stock Exchange.The population in this study are manufacturing companies in the food and beverage sector that have been listed on the Indonesia Stock Exchange in 2018, 2019, and 2020. And after using the purpose sampling method, 11 companies were obtained that match the criteria to be used as research samples. The data is then processed using the multiple linear regression method.The results of this study reveal that profitability, firm size, and rewards have a significant positive effect on the Corporate Social Responsibility Disclosure.